Microstructure, Physical and Biological Properties, and BSA Binding Investigation of Electrospun Nanofibers Made of Poly(AA-co-ACMO) Copolymer and Polyurethane - Mansour, Hanaa; Elsigeny, Samia M.; Elshami, Fawzia I.; Auf, Mohamed; Shaban, Shaban Y.; van Eldik, Rudi (Molecules, 2023)
In this study, poly(AA-co-ACMO) and polyurethane-based nanofibers were prepared in a ratio of 1:1 (NF11) and 2:1 (NF21) as antimicrobial carriers for chronic wound management. Different techniques were used to characterize the nanofibers, and poly(AA-co-ACMO) was mostly found on the surface of PU. With an increase in poly(AA-co-ACMO) dose from 0 (PU) and 1:1 (NF11) to 2:1 (NF21) in the casting solution, the contact angle (CA) was reduced from 137 and 95 to 24, respectively, and hydrophilicity was significantly increased. As most medications inhibit biological processes by binding to a specific protein, in vitro protein binding was investigated mechanistically using a stopped-flow technique. Both NF11 and NF21 bind to BSA via two reversible steps: a fast second-order binding followed by a slow first-order one. The overall parameters for NF11 (Ka = 1.1 × 104 M−1, Kd = 89.0 × 10−6, ΔG0 = −23.1 kJ mol−1) and NF21 (Ka = 189.0 × 104 M−1, Kd = 5.3 × 10−6 M, ΔG0 = −27.5 kJ mol−1) were determined and showed that the affinity for BSA is approximately (NF11)/(NF21) = 1/180. This indicates that NF21 has much higher BSA affinity than NF11, although BSA interacts with NF11 much faster. NF21 with higher hydrophilicity showed effective antibacterial properties compared to NF11, in agreement with kinetic data. The study provided an approach to manage chronic wounds and treating protein-containing wastewater.
CRIS-Team Scopus Importer:2023-05-26
Keywords: antibacterial; BSA-affinity; electrospun; hydrophilic; nanofiber; poly(acrylic acid-co-acryloylmorpholine); wound healing